Selective left mainstem bronchial intubation in the neonatal intensive care unit - Anthony M.H. Ho; Michael P. Flavin; Melinda L. Fleming; Glenio Bitencourt Mizubuti (Brazilian Journal of Anesthesiology, 2018)
Background: Selective neonatal left mainstem bronchial intubation to treat right lung disease is typically achieved with elaborate maneuvers, instrumentation and devices. This is often attributed to bronchial geometry which favors right mainstem entry of an endotracheal tube deliberately advanced beyond the carina. Case summary: A neonate with severe bullous emphysema affecting the right lung required urgent non-ventilation of that lung. We achieved left mainstem bronchial intubation by turning the endotracheal tube 180° such that the Murphy's eye faced the left instead of the right, and simulated a left-handed intubation by slightly orientating the endotracheal tube such that its concavity faced the left instead of the right as in a conventional right-handed intubation. Conclusion: Urgent intubation of the left mainstem bronchus with an endotracheal tube can be easily achieved by recognizing that it is the position of the endotracheal tube tip and the direction of its concavity that are the chief determinants of which bronchus an endotracheal tube goes when advanced. This is important in critically ill neonates as the margin of safety and time window are small, and the absence of double-lumen tubes. Use of fiberoptic bronchoscope and blockers should be reserved as backup plans. Resumo: Justificativa: A intubação seletiva neonatal do brônquio principal esquerdo para tratar a doença pulmonar direita é tipicamente realizada com elaboradas manobras, instrumentação e dispositivos. Isso é frequentemente atribuído à geometria brônquica que favorece a entrada principal direita de um tubo endotraqueal (TET) deliberadamente avançado para além da carina. Resumo do caso: Recém-nascido com enfisema bolhoso grave afetando o pulmão direito que precisou com urgência da não ventilação desse pulmão. Conseguimos a intubação brônquica esquerda fazendo uma rotação de 180° do TET, de forma que o olho de Murphy ficasse voltada para a esquerda e não para a direita, e simulamos uma intubação à esquerda orientando ligeiramente o TET, de modo que sua concavidade virasse para a esquerda em vez de para a direita, como em uma intubação convencional à direita. Conclusão: A intubação urgente do brônquio principal esquerdo com um TET pode ser facilmente obtida reconhecendo-se que é a posição da ponta do TET e a direção de sua concavidade que determinam para qual brônquio o TET irá quando avançado. Isso é importante em neonatos criticamente doentes diante da margem de segurança e janela de tempo pequenas e na ausência de tubos de duplo lúmen. O uso de broncofibroscópio e bloqueadores deve ser considerado como planos de segurança. Keywords: Bullous emphysema, Endobronchial intubation, Neonate, Palavras-chave: Enfisema bolhoso, Intubação endobrônquica, Recém-nascido